Koncepcja rozwoju Wojewódzkiego Ośrodka Sportu i Rekreacji w Drzonkowie „Farma Zdrowia” = The Concept of Development of Voivodeship Sport and Recreation Centre in Drzonkow “Health Farm” - Mrozkowiak, Mirosław; Mrozkowiak, Magdalena; Mrozkowiak, Marta (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław, Mrozkowiak Magdalena, Mrozkowiak Marta. Koncepcja rozwoju Wojewódzkiego Ośrodka Sportu i Rekreacji w Drzonkowie „Farma Zdrowia” = The Concept of Development of Voivodeship Sport and Recreation Centre in Drzonkow “Health Farm”. Journal of Education, Health and Sport. 2015;5(11):405-418. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34231 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A405-418 https://pbn.nauka.gov.pl/works/672056 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 24.11.2015. Koncepcja rozwoju Wojewódzkiego Ośrodka Sportu i Rekreacji w Drzonkowie „Farma Zdrowia” The Concept of Development of Voivodeship Sport and Recreation Centre in Drzonkow “Health Farm” Mirosław Mrozkowiak, Magdalena Mrozkowiak, Marta Mrozkowiak Bioergonsport, Nowa Biała 8p, 09-411 Biała Słowa kluczowe: sport, rekreacja. Streszczenie Ośrodek w Drzonkowie zawsze przyciągał mieszkańców nie tylko Regionu Lubuskiego. Z jego bazy treningowej korzystają sportowcy polscy i zagraniczni. Niestety z biegiem lat wskutek stopniowej dekapitalizacji obiektów i licznych zmian organizacyjnych, funkcjonalność Wojewódzkiego Ośrodka Sportu i Rekreacji przestała odpowiadać współczesnym standardom. Struktura organizacyjna i niewydolne zarządzanie nie zahamowały tego procesu. Ośrodek musi być wielofunkcyjny i powszechnie dostępny. Powinien spełniać oczekiwania mieszkańców nie tylko regionu. Opracowanie szczegółowych założeń modernizacji WOSiR, w zakresie przyszłych funkcji i procesu inwestycyjnego będzie pierwszym krokiem w kierunku naprawy i rozwoju. Krok drugi, to inwestycje własne i wdrożenie partnerstwa społeczno - prywatnego, które pozwoli na szybkie i oszczędne sfinalizowanie zamierzeń. Wizja rozwoju ośrodka jest możliwa do realizowania dzięki dotychczas dokonanym przedsięwzięciom, których zrealizowanie było możliwe przy wsparciu finansowemu organu założycielskiego, środkom pozyskanym z funduszy pomocowych, sponsorów i działań własnych. Dyrekcja dobrze zaplanowała i wykorzystała środki pomocowe przekazane na modernizację bazy hotelowej i sportowej, jednak zmiany muszą być radykalne. Keywords: sport, recreation. Abstract The Voivodeship Sport and Recreation Centre (Wojewódzki Ośrodek Sportu i Rekreacji, WOSiR) in Drzonkow has always attracted inhabitant of both Lubusz Voivodeship and other regions of the country. Its sports facilities are used by Polish and foreign sportsmen. Unfortunately, in the course of time, as a result of gradual decapitalization of sports centres and numerous organizational transitions, functions of the Voivodeship Sport and Recreation Centre stopped meeting contemporary standards. Organizational structure and inefficient management did not prevent development of this process. The sport and recreation centres must meet the criteria of being multifunctional and readily available. It should meet expectations of both inhabitants and people from other regions. Development of detailed assumptions for modernization of WOSiR in terms of its future functionalities and investment process will become the first step towards improvement and development. Second step includes own investments and implementation of public and private partnership, which will allow for quick and economical realization of the objectives. Vision of development of the centre is possible to be realized with projects implemented so far, whose realization was possible using financial support from foundation body, funds obtained from aid funds, sponsoring and own initiatives. The management have properly planned and used aid resources allocated for modernization of hotel and sport facilities, however, the transitions have to be more radical.